2010
DOI: 10.1007/s00534-010-0268-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal oncocytic papillary neoplasms of the pancreas and bile ducts: a description of five new cases and review based on a systematic survey of the literature

Abstract: Background Intraductal oncocytic papillary neoplasms (IOPN) are rare tumors of the pancreatic and biliary ductal system. It is not absolutely clear if the molecular and clinicopathologic characteristics of IOPN differ significantly from other related lesions, namely intraductal papillary mucinous neoplasms (IPMN). Therefore it is not clear if it is reasonable to consider IOPN as a separate diagnostic and clinical entity. Methods In order to describe the clinicopathologic characteristics of IOPN and to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 78 publications
(329 reference statements)
2
37
0
Order By: Relevance
“…1 In a study of 283 IPMNs, Furukawa et al 6 reported a mean age of 60.3 years for 24 patients with IOPN, compared to 65.6, 64.5, and 69.2 years for gastric, intestinal, and pancreatobiliary types, respectively, and suggested an increased likelihood of earlier onset of IOPNs compared with that of the other histologic subtypes. However, other studies 9,10 have not reported a significant age difference. For example, a review by Liszka et al 10 of 24 pancreatic IOPN cases reported a mean age of 63.9 years with no significant age or sex differences between IOPN and IPMN overall.…”
Section: Clinical Featuresmentioning
confidence: 69%
See 4 more Smart Citations
“…1 In a study of 283 IPMNs, Furukawa et al 6 reported a mean age of 60.3 years for 24 patients with IOPN, compared to 65.6, 64.5, and 69.2 years for gastric, intestinal, and pancreatobiliary types, respectively, and suggested an increased likelihood of earlier onset of IOPNs compared with that of the other histologic subtypes. However, other studies 9,10 have not reported a significant age difference. For example, a review by Liszka et al 10 of 24 pancreatic IOPN cases reported a mean age of 63.9 years with no significant age or sex differences between IOPN and IPMN overall.…”
Section: Clinical Featuresmentioning
confidence: 69%
“…However, other studies 9,10 have not reported a significant age difference. For example, a review by Liszka et al 10 of 24 pancreatic IOPN cases reported a mean age of 63.9 years with no significant age or sex differences between IOPN and IPMN overall.…”
Section: Clinical Featuresmentioning
confidence: 69%
See 3 more Smart Citations